Technological rationalization of fermented ice cream production - Mykhalevych, Artur; Sapiga, Victoria; Polishchuk, Galyna; Osmak (Fedchenko), Tetiana (Technological rationalization of fermented ice cream production / A. Mykhalevych, V. Sapiga, G. Polischuk, T. Osmak // Proceedings of the ІІ International Conference on European Dimensions of Sustainable Development, June 26, 2020. – Kyiv : NUFT, 2020. – P. 98., 2020)
In recent years, the volume of production of health food products is growing, their caloric content is decreasing, and the share of ingredients with therapeutic or prophylactic properties in their composition is increasing. Therefore, instead of milk as a milk base in the ice cream, it is advisable to use secondary dairy resources - skim milk, buttermilk and whey, which was fermented by probiotic acidophilic starter, contain biologically complete proteins and can be further enriched with pectin-containing raw materials.
Keywords: fermented; ice cream; skim milk; ферментований; морозиво; знежирене молоко; кафедра технології молока і молочних продуктів